Feline pulmonary histiocytic sarcoma associated with passive smoking in a 14-year-old neutered male cat - Ongko, Michelle Virginia; Setiawati, Ayu; Putra, Maulana Ar Raniri; Siallagan, Sitaria Fransiska; Utami, Reginta Putri; Sembiring, Ester Br (ARSHI Veterinary Letters, 2025)
Pulmonary histiocytic sarcoma is a rare, aggressive neoplasm associated with poor clinical outcomes in cats. This report describes a 14-year-old neutered male domestic cat who developed pulmonary histiocytic sarcoma after chronic exposure to secondhand tobacco smoke. The cat presented with persistent cough, inappetence, and progressive dyspnea. Diagnostic evaluation using thoracic radiography and cytological examination revealed neoplastic proliferation, consistent with histiocytic sarcoma. Despite supportive therapy, the cat's condition deteriorated, and euthanasia was elected because of grave prognosis. This case highlights the oncogenic impact of passive smoking on companion animals and the need for public awareness of smoke-free environments for pet health. Further studies are required to elucidate how environmental carcinogens, particularly tobacco smoke, contribute to cancer pathogenesis in domestic species.